2010
DOI: 10.1371/journal.pone.0012872
|View full text |Cite
|
Sign up to set email alerts
|

Light Chain Separated from the Rest of the Type A Botulinum Neurotoxin Molecule Is the Most Catalytically Active Form

Abstract: Botulinum neurotoxins (BoNT) are the most potent of all toxins. The 50 kDa N-terminal endopeptidase catalytic light chain (LC) of BoNT is located next to its central, putative translocation domain. After binding to the peripheral neurons, the central domain of BoNT helps the LC translocate into cytosol where its proteolytic action on SNARE (soluble NSF attachment protein receptor) proteins blocks exocytosis of acetyl choline leading to muscle paralysis and eventual death. The translocation domain also contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…The greater potency of self‐activated LH N /A in eSCNs may be attributable to the dissociated LC/A becoming free of H N /A. This is in agreement with the higher specific activity of the LC/A moiety compared to LH N /A and BoNT/A [21].…”
Section: Discussionsupporting
confidence: 59%
“…The greater potency of self‐activated LH N /A in eSCNs may be attributable to the dissociated LC/A becoming free of H N /A. This is in agreement with the higher specific activity of the LC/A moiety compared to LH N /A and BoNT/A [21].…”
Section: Discussionsupporting
confidence: 59%
“…In light of the inhibitor development problems, we extended that study to include two C-terminally truncated LcA and demonstrated that a full length BoNT/A Lc containing 1–448 residues has the highest catalytic activity because its C-terminal appeared to play a product removal role from the active site of LcA [24]. There was little variation in the substrate K m catalyzed by these Lcs and by various BoNT/A forms [25].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the BoNT/A LC is catalytically active only after translocation into the neuronal cytosol and dissociation from the HC. Experimental evidence indicates that the BoNT/A LC, after separation from the rest of the holotoxin, is the actual active component [ 47 ]. In contrast, the orientation of the BoNT/B protective belt allows for active site access relative to the BoNT/A holotoxin [ 39 ], making the BoNT/B LC catalytically active prior to reduction of the disulfide bond.…”
Section: Crystal Structures Of Botulinum Neurotoxinsmentioning
confidence: 99%